Effect of Adding Palm Kernel Cake as a Substrate in Sclerotium rolfsii Inoculum - Fajrona, Kadran; Rizal, Yose; Mirnawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
This research aims to determine the added palm kernel cake (PKC) level in the Sclerotium rolfsii inoculum. This research used an experimental method with a completely randomized design, four treatments, and five replications. The treatments were different substrate compositions, consisting of 100% bran (control), 90% bran + 10% PKC (P1), 85% bran + 15% PKC (P2), and 80% bran + 20% PKC (P3). The variables observed were cellulase and mannanase enzyme activities. The data obtained were analyzed statistically using a completely random design analysis of variance and continued with Duncan's multiple range tests if the treatment influenced the observed variables. The results showed that adding PKC as a substrate in making Sclerotium rolfsii inoculum had a significant effect (P<0.01) on the activity of cellulase and mannanase enzymes. The best cellulase and mannanase enzyme activities were found in the 80% fine bran substrate composition + 20% PKC (P3), namely 16.02 U/mL and 7.81 U/mL.